2004
DOI: 10.1509/jmkg.68.1.73.24037
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Governance in a Supply Chain Network

Abstract: The authors examine how a firm's strategy in a (downstream) customer relationship is contingent on how a related relationship outside of the focal dyad is organized. Drawing on emerging perspectives on interfirm governance and networks, the authors propose that the ability to show flexibility toward a (downstream) customer under uncertain market conditions depends on the governance mechanisms that have been deployed in an (upstream) supplier relationship. The governance mechanisms take the form of (1) supplier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
347
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(361 citation statements)
references
References 91 publications
(122 reference statements)
5
347
0
9
Order By: Relevance
“…Although literature from the relational perspective has acknowledged that relationships with multiple stakeholders matter and that insights from the relationship marketing literature may be helpful in understanding relationships with non-customer stakeholders as well (Grönroos 1990;Berry 1995;Payne and Frow 2005), most of the marketing discipline has not fully embraced this notion and has kept the customer in the focus of attention. Similarly, most studies taking a relational perspective on supply chains have focused on the buyer-supplier dyad, although some authors have started to investigate the networks in which relationships exist (e.g., Wathne and Heide 2004). We argue that the marketing discipline should move further away from its rather restrictive focus on customers toward a view of marketing that embraces other stakeholders and the interrelations between them.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although literature from the relational perspective has acknowledged that relationships with multiple stakeholders matter and that insights from the relationship marketing literature may be helpful in understanding relationships with non-customer stakeholders as well (Grönroos 1990;Berry 1995;Payne and Frow 2005), most of the marketing discipline has not fully embraced this notion and has kept the customer in the focus of attention. Similarly, most studies taking a relational perspective on supply chains have focused on the buyer-supplier dyad, although some authors have started to investigate the networks in which relationships exist (e.g., Wathne and Heide 2004). We argue that the marketing discipline should move further away from its rather restrictive focus on customers toward a view of marketing that embraces other stakeholders and the interrelations between them.…”
Section: Introductionmentioning
confidence: 95%
“…Relationship marketing has been shown to be of strategic importance for firms in the customer relationship management literature (Reinartz et al 2004;Payne and Frow 2005). In a supply chain context, research has yielded insights in the nature of relationships between firms (Cannon and Perreault 1999;Wathne and Heide 2004). In a business-to-business setting a network approach has been used to understand the embedded context of dyadic relationships (Anderson et al 1994).…”
Section: Implications For Marketing Theorymentioning
confidence: 99%
“…That the impact of contract governance depends on the institutional environment. On the other hand, because supply chain relationships are embedded in a macro-social environment [20]. Successful supply chain governance often depends on supportive institutional frameworks, including legal systems and government.…”
Section: The Regulatory Role Of Institutional Pressurementioning
confidence: 99%
“…The importance of relational contract for supplier -buyer relationship which in turn affects supply chain performance has been emphasized by Chuah et al (2010). Based on the predictions of Transaction Cost Analysis (TCA), Wathne and Heide (2004) explain that governance can improve focal company's performance. These authors have clearly identified sustainable performance to result from supplier evaluation, selection and development.…”
Section: Research Question 01mentioning
confidence: 99%
“…It involves control and coordination. Wathne and Heide (2004) argue that where there is no governance exercised in upstream relationships it will negatively influence the manufacturer's ability to respond to uncertainty in the downstream market. Carey and Lawson (2011) too share a similar view when they say that the performance of the supply chain can be improved with the social capital built up through enhanced supplier relationships (Nahapiet and Ghoshal, 1998).…”
Section: Introductionmentioning
confidence: 99%